1992
DOI: 10.1056/nejm199211123272002
|View full text |Cite|
|
Sign up to set email alerts
|

Warfarin in the Prevention of Stroke Associated with Nonrheumatic Atrial Fibrillation

Abstract: Low-intensity anticoagulation with warfarin prevented cerebral infarction in patients with nonrheumatic atrial fibrillation without producing an excess risk of major hemorrhage. This benefit extended to patients over 70 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
282
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,183 publications
(298 citation statements)
references
References 17 publications
6
282
1
9
Order By: Relevance
“…[1][2][3][4][8][9][10][11] Warfarin decreases the risk of stroke by 64% to 86% compared with placebo. [12][13][14][15][16] Warfarin has also been associated with decreased total health care costs among patients with AF in comparison with patients who were not taking warfarin. 17 However, despite its many benefits, warfarin is associated with adverse events, particularly bleeding and its resulting costs, which likely play a substantive role in warfarin nonpersistence (i.e., discontinuation or interruption).…”
Section: ■■ Methods Study Designmentioning
confidence: 99%
“…[1][2][3][4][8][9][10][11] Warfarin decreases the risk of stroke by 64% to 86% compared with placebo. [12][13][14][15][16] Warfarin has also been associated with decreased total health care costs among patients with AF in comparison with patients who were not taking warfarin. 17 However, despite its many benefits, warfarin is associated with adverse events, particularly bleeding and its resulting costs, which likely play a substantive role in warfarin nonpersistence (i.e., discontinuation or interruption).…”
Section: ■■ Methods Study Designmentioning
confidence: 99%
“…We chose the meta-analysis by Hart et al,136 as it is the most recent and comprehensive. Hart et al 136 identified six studies [137][138][139][140][141][142] comparing warfarin to either 'control' or placebo, from which we extracted evidence on stroke, bleeds, ICH, death, SE and TIA, summarised in Table 60. The Boston Area Anticoagulation Trial for Atrial Fibrillation (BAATAF) study 139 used patients on no treatment but with the option of aspirin as the control; this study was omitted in a sensitivity analysis.…”
Section: Relative Treatment Efficacymentioning
confidence: 99%
“…However, warfarin was prescribed to replace aspirin as it is more benefitted to patient with stroke risk score more than 2 and could reduce the risk of stroke by two-thirds and mortality by one-quarter compared to aspirin use. [19][20][21][22][23] Subsequent doses of warfarin dependent on the prothrombin time, reported as INR (international normalised ratio). Hence, regular testing of the INR in first three months of treatment is essential for patient who never received warfarin.…”
Section: Discussionmentioning
confidence: 99%